INFORMATION EXTRACTION FROM MULTISPECTRAL SATELLITE IMAGES: INFORMATION EXTRACTION FROM MULTISPECTRAL SATELLITE IMAGES - Zdravcheva, Neli (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article analyzes various methods and approaches of modern remote sensing that can be used in the processing of multispectral satellite images in order to effectively extract visual information about territories for which preliminary data is not available. Attention is paid to the creation of new derivative images (synthesized and indexed) and to performing pixel-oriented computer non supervised classification. A series of experiments have been made that clearly reveal the advantages and conveniences of remote retrieval of information from multispectral satellite images in a territory for which reference objects and other data acquired in situ are not available.